Electronic commerce : security, risk management, and control - Greenstein, Marilyn; Feinman, Todd M. (Boston : Irwin/McGraw-Hill, New Delhi : Tata McGraw-Hill, 2000)
This textbook aims to equip the reader with knowledge and understanding of electronic commerce from a security risk management and control perspective. It uses real-world examples to reinforce learning.
"First edition"--P. ix.
Teaching aids available to accompany text: PowerPoint slides, Solutions manual, course web site.
Includes bibliographical references and index.
oif 19/02/15
Loans
Keywords: Electronic commerce; Business enterprises; Risk management